Service users' perspective of their admission: a report of study findings. (8th March 2016) - O'Donoghue, B.; Roche, E.; Lyne, J.; Madigan, K.; Feeney, L.
Abstract : Objectives: The 'Service Users' Perspective of their Admission' study examined voluntarily and involuntarily admitted services users' perception of coercion during the admission process and whether this was associated with factors such as the therapeutic alliance, satisfaction with services, functioning and quality of life. This report aims to collate the findings of the study. Methods: The study was undertaken across three community mental health services in Ireland. Participants were interviewed before discharge and at 1 year using the MacArthur Admission Experience. Caregivers of participants were interviewed about their perception of coercion during the admission. Results: A total of 161 service users were interviewed and of those admitted involuntarily, 42% experienced at least one form of physical coercion. Service users admitted involuntarily reported higher levels of perceived coercion and less procedural justice than those admitted voluntarily. A total of 22% of voluntarily admitted service users reported levels of perceived coercion comparable with involuntarily admitted service users and this was associated with treatment in a secure ward or being brought to hospital initially under mental health legislation. In comparison with the service user, caregivers tended to underestimate the level of perceived coercion. The level of procedural justice was moderately associated with the therapeutic relationship and satisfaction with services. After 1 year, 70% experienced an improvement in functioning and this was not associated with the accumulated level of coercive events, when controlled for confounders. Conclusions: This study has provided valuable insights into the perceptions of coercion and can help inform future interventional studies aimed at reducing coercion in mental health services.